Syntheses of organic medicinal compounds - Ishar, M. ([S.l.] : Alpha Science Intl Ltd, 2006)
Syntheses of Organic Medicinal Compounds incorporates synthetic and semi-synthetic routes to large number of organic medicinal compounds including a number of new drugs. Each section has been divided in to sub-sections based either on chemical structures or modes of action. The objective is to enable easy comprehension of synthetic routes to similar molecular entities. Emphasis has been to include all the varied examples from each class of drugs so as to give widest possible coverage to synthetic methodology to structurally similar molecular frameworks.
Keywords: syntheses,organic medicinal compounds